2022
DOI: 10.1186/s12889-022-12546-w
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to initiating and maintaining participation in parkrun

Abstract: Interventions that increase population physical activity are required to promote health and wellbeing. parkrun delivers community-based, 5 km events worldwide yet 43% who register never participate in a parkrun event. This research had two objectives; i) explore the demographics of people who register for parkrun in United Kingdom, Australia, Ireland, and don’t initiate or maintain participation ii) understand the barriers to participating in parkrun amongst these people. Mandatory data at parkrun registration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 27 publications
7
17
4
Order By: Relevance
“…Return rates to parkrun The overall return rate of 64.18% is higher than the 61.95% reported in an earlier study [13].…”
Section: Discussioncontrasting
confidence: 64%
“…Return rates to parkrun The overall return rate of 64.18% is higher than the 61.95% reported in an earlier study [13].…”
Section: Discussioncontrasting
confidence: 64%
“…Individual participants increase their performance revealing tness bene ts of participating in parkrun. Women are known to have greater barriers to engaging in sporting activity and a recent study has revealed that this also applies to parkrun [30]. This study reveals that women are more likely to attend remoter events on slower surfaces.…”
Section: Discussionmentioning
confidence: 64%
“…Individual participants improve their performance, revealing the fitness benefits of participating in parkrun. Women are known to have greater barriers to engaging in sporting activity, and a recent study has revealed that this also applies to parkrun [ 30 ]. This study reveals that women are more likely to attend remoter events on slower surfaces.…”
Section: Discussionmentioning
confidence: 99%